2019
DOI: 10.1093/mnras/stz1706
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of AGN activity on environment in SDSS

Abstract: Environment is one of the key external drivers of the galaxies, while active galactic nucleus (AGN) is one of the key internal drivers. Both of them play fundamental roles in regulating the formation and evolution of galaxies. We explore the interrelationship between environment and AGN in SDSS. At a given stellar mass, the specific star formation rate distribution of the AGN host galaxies remains unchanged with overdensity, with the peak of the distribution around the Green Valley. We show that, at a given st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 108 publications
2
20
0
2
Order By: Relevance
“…This results in non-AGN galaxies being included in the AGN samples and the statistics would be biased towards regular galaxy distributions and thus not representative of the AGN population -an issue also raised by Hainline et al (2016) Furthermore, while the environment estimation methods used in this study are tried and tested in other work for other purposes, there is a risk that they do not properly gauge the desired properties or the properties are not showing up in the statistics due to obfuscating factors such as trigger time lag (the time delay it takes for AGN activity to begin after an interaction or harassment event, see e.g Schawinski et al 2007;Pimbblet et al 2013;Shabala et al 2012Shabala et al , 2017 or SF contamination (Trump et al 2015). Other environment estimation methods may reveal a connection to AGN activity, but the findings in this paper are in line with existing literature (e.g Miller et al 2003;Kauffmann et al 2004;Padilla et al 2010;Sabater et al 2013;Sabater et al 2015;Man et al 2019). Therefore, using other relatively simple environment estimates will likely show similar results but more complicated ones such as the so-called tidal force estimator may find a difference in immediate environment (Sabater et al 2013).…”
Section: On the Environment And Nearest Neighbourssupporting
confidence: 77%
“…This results in non-AGN galaxies being included in the AGN samples and the statistics would be biased towards regular galaxy distributions and thus not representative of the AGN population -an issue also raised by Hainline et al (2016) Furthermore, while the environment estimation methods used in this study are tried and tested in other work for other purposes, there is a risk that they do not properly gauge the desired properties or the properties are not showing up in the statistics due to obfuscating factors such as trigger time lag (the time delay it takes for AGN activity to begin after an interaction or harassment event, see e.g Schawinski et al 2007;Pimbblet et al 2013;Shabala et al 2012Shabala et al , 2017 or SF contamination (Trump et al 2015). Other environment estimation methods may reveal a connection to AGN activity, but the findings in this paper are in line with existing literature (e.g Miller et al 2003;Kauffmann et al 2004;Padilla et al 2010;Sabater et al 2013;Sabater et al 2015;Man et al 2019). Therefore, using other relatively simple environment estimates will likely show similar results but more complicated ones such as the so-called tidal force estimator may find a difference in immediate environment (Sabater et al 2013).…”
Section: On the Environment And Nearest Neighbourssupporting
confidence: 77%
“…Other groups measured a f AGN sat consistent with zero 69 . More recently Man et al 73 found the SDSS completeness-corrected fraction of local AGN at fixed stellar mass is independent of environment, with the fraction of AGN in satellite galaxies being comparable, if not lower, than that in central galaxies (see their Figure 4). The Man et al results would imply Q bh 1 largely independent of host stellar mass, as assumed here.…”
Section: Resultsmentioning
confidence: 92%
“…In this regard, quite different results have been obtained, variously reporting enhancement, decrease or no change in AGN activity at dense environments (Miller et al 2003;Kauffmann et al 2004;Gilmour et al 2007;Bradshaw et al 2011;Malavasi et al 2015;Manzer & De Robertis 2014;Koulouridis et al 2018). The discrepancies in the results are likely to be because of fundamental differences in powering AGN at different wavelengths as discussed above, differences in definitions of AGN activity (Man et al 2019) and environment or due to the possible biases in the samples of AGN which compare different environments. The latter suggests these results need to be studied for different types of galaxies, because AGN activity has been shown to be a strong function of host galaxy properties such as mass or colour (Best et al 2005b;Janssen et al 2012) and host galaxy properties are strong functions of environment (Balogh et al 2004;Baldry et al 2006).…”
Section: Agnmentioning
confidence: 99%